Penerapan Sistem Informasi Pemasaran Toko Oleh-Oleh Makanan Khas Danau Maninjau Berbasis WEB - Wizra Aulia; Stefani Hardiyanti Putri; Imelda Juniarta Emin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Lake Maninjau specialty food souvenir shop is one of the micro businesses that sells a variety of traditional regional food products. So far, the marketing process and transaction management are still done manually, which causes limited market reach, difficulty in recording sales, and lack of effectiveness in product promotion. This research aims to design a web-based marketing information system to support the sales process, promotion, and data management in a more efficient and integrated manner. The system development method uses the System Development Life Cycle (SDLC) approach of the waterfall model, which includes the planning, needs analysis, system design, implementation, and testing stages. Data collection was conducted through field observations, interviews with business owners, questionnaires to customers, and literature studies related to information systems and digital marketing strategies. The designed information system includes various main features such as product data management, sales transaction recording, automatic sales report generation, social media integration, and product promotion pages. In the marketing aspect, this system allows businesses to display product catalogs online, provide real-time promotional information, and establish direct interaction with customers through contact and ordering features. In addition, the use of this system allows stores to reach a wider market, including potential customers from outside the Lake Maninjau area, through an integrated digital marketing strategy. The implementation results show that this web-based system can increase the effectiveness of product promotion, speed up the transaction process, and improve the quality of customer service. With this system, souvenir shops can compete more competitively in the digital era, as well as strengthen brand image and customer loyalty through more structured and sustainable marketing.